Al-Jarh Wa Al -Ta’dil Dalam Studi Hadis: Metode Penilaian Perowi Hadis - Dwi Agustin; Dewi Kumala Sari; Muhammad Nasir; Akhmad Supriadi (CV. ITTC INDONESIA, 2026)
Al-Jarh wa Al-Ta'dil is a branch of hadith science which plays an important role in assessing the credibility of narrators and determining the quality of a hadith. This science was developed by the ulama as an effort to maintain the authenticity of hadith from various forms of deviation, error and forgery that can occur in the process of narration. This article aims to examine the concept of Al-Jarh wa Al-Ta'dil, a method for evaluating hadith narrators, as well as its contribution in maintaining the authenticity of hadith as a source of Islamic teachings after the Qur'an. This research uses a library research method by analyzing various classical and contemporary literature related to hadith science and rijal science. The results of the study show that the assessment of narrators is carried out based on the criteria of fairness (al-'ilah) and accuracy (al-dhabt), as well as through the systematic application of the rules of Al-Jarh wa Al-Ta'dil. Thus, the science of Al-Jarh wa Al-Ta'dil becomes a very important scientific instrument in selecting hadith, distinguishing acceptable and rejected hadith, and maintaining the purity of Islamic teachings throughout the ages.